2018
DOI: 10.1016/j.ijcard.2017.12.016
|View full text |Cite
|
Sign up to set email alerts
|

The impact of delayed treatment on 6-minute walk distance test in patients with pulmonary arterial hypertension: A meta-analysis

Abstract: A short-term delay in PAH targeted therapy may adversely affect functional capacity in patients with PAH. This meta-analysis provides some insight as to whether earlier treatment would benefit stable patients with PAH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 21 publications
0
24
0
Order By: Relevance
“…A meta-analysis of six PAH short-term RCTs showed that the placebo group never "caught up" to the active group in terms of 6-min walk distance following open label therapy. 17 This suggests that a treatment delay of 12 to 16 weeks may have a long-term effect on functional capacity and outcome.…”
Section: Lost Ground May Not Be Regainedmentioning
confidence: 99%
“…A meta-analysis of six PAH short-term RCTs showed that the placebo group never "caught up" to the active group in terms of 6-min walk distance following open label therapy. 17 This suggests that a treatment delay of 12 to 16 weeks may have a long-term effect on functional capacity and outcome.…”
Section: Lost Ground May Not Be Regainedmentioning
confidence: 99%
“…The publication year ranged between 2007 [ 43 ] and 2020 [ 39 , 41 , 48 , 67 ] with most studies published in recent years. MAs were conducted in 35 studies [ 17 , 19 , 20 , 22 , 23 , 26 29 , 31 , 35 41 , 43 47 , 49 51 , 53 , 56 , 58 60 , 63 66 , 69 ], NMAs in 15 studies [ 18 , 21 , 24 , 25 , 30 , 32 , 33 , 42 , 48 , 52 , 54 , 57 , 61 , 62 , 67 ], both NMA and MA in one study [ 55 ], and MA and disproportionality analysis in one study [ 34 ]. Of 52 studies, 47 evaluated the impact of PAH interventions in patients with PAH and PAH subgroups (based on aetiology, e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Further critical appraisal performed based on input from clinical experts. Vizza 2018 [ 56 ] Patients with PAH MA 6 Oral bosentan, oral ambrisentan, oral riociguat, oral tadalafil and oral/inhaled treprostinil 6MWD Not reported Wang 2018 e [ 57 ] Patients with PAH NMA 45 Oral ERAs (ambrisentan, bosentan, macitentan, sitaxsentan), oral PDE5Is (sildenafil, tadalafil, vardenafil d ), prostanoids (IV epoprostenol, oral/IV/inhaled/SC treprostinil, inhaled iloprost, oral beraprost), sGCSs (oral riociguat), sPRA (oral selexipag) 6MWD, WHO FC, BDI, cardiac index, PAP, RAP, PVR, clinical worsening, hospitalization, death, SAEs, and withdrawal Not reported Wei 2016 [ 58 ] Patients with different diseases including PAH MA 24 Oral ERAs (bosentan, ambrisentan and macitentan); EU authorised AEs Cochrane’s risk of bias and GRADE for evidence Xing 2011 [ 59 ] Patients with PAH (including idiopathic PAH, familial PAH, as well as CTD-associated PAH, pulmonary shut, portal hypertension, HIV infection and thyroid disease) MA 10 Prostanoids (IV epoprostenol, IV/SC treprostinil, oral beraprost and inhaled iloprost) 6MWD, BDI, cardiac index, mean PAP, PVR, mortality, clinical worsening and AEs Jadad scores Zhang 2015 [ 60 ] Patients with PAH MA 21 Oral treatments (ambrisentan, bosentan, macitentan, sitaxentan, sildenafil, tadalafil, riociguat, beraprost, epoprostenol, treprostinil, terbogrel d and imatinib d ) CCW or at least all-cause mortality Cochrane’s risk of bias Zhang 2016 [ 61 ] Patients with PAH NMA 14 Prostanoids (IV epoprostenol, inhaled/IV/oral/SC treprostinil, oral beraprost and inhaled iloprost) 6MWD, mortality, Functional Class, and discontinuation Not reported Zhang 2019 [ 62 ] Patients with PAH NMA 10 Oral ERAs (bosentan, ambrisentan, macitentan) Safety outcomes: abnormal li...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite advances in treatment, pulmonary hypertension (PH) remains a progressive life-limiting disease ( 1 ). Studies have suggested that earlier intervention results in better outcomes ( 2 , 3 ). However, patients are usually diagnosed when the disease is advanced ( 4 , 5 ) and consequently there is interest in developing strategies to enable earlier diagnosis ( 6 ).…”
Section: Introductionmentioning
confidence: 99%